"Dedicado a Mi Familia": The Role of Familismo on Academic Outcomes Among Latinx College Students. Issue 4 (August 2022) - Azpeitia, Jovani; Bacio, Guadalupe A.
Addressing the retention and support of Latinx college students is imperative given their low graduation rates despite increasing enrollment. We sought to extend our understanding of the effects of familismo (i.e., the sense of providing support, acting in reference, and feeling an obligation to the family) on academic outcomes among Latinx college students by examining the roles of immigrant generation and gender. Latinx college students ( N = 176) from highly selective and predominantly White institutions completed self-report measures on familismo, academic motivation, and ganas . Familismo positively predicted academic motivation for first-generation Latinos and second-generation Latinas, suggesting that this association differs by immigrant generation and gender. Findings revealed that familism support most closely predicted academic motivation. Understanding the factors that promote academic motivation among Latinx college students, rather than those that hinder it, is crucial to addressing the disparities in attaining a higher education faced by this growing and diverse community.